The Effectiveness of Training Bowen\'s Family Therapy Approach on Marital Satisfaction of Married Women in AligodarzCity (In the West of Iran), in 2019 - saeedeh mehrabi; sahar khanjani veshki (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Marital satisfaction is one of the most important signs of a favorable relationship between couples.This research aimed to survey the effectiveness of training using Bowen's family therapy approach on marital satisfaction of married women in the city of Aligodarz(In the west of Iran). Methods: This study was aquasi experimental study using a pretest-posttest design with a control group that were done  inAligodarzcity in 2019. by convenience sampling, 30 married women were selected and participated in this study. After recording the subjects' scores in the pre-test stage, the experimental group was exposed to the independent variable, but no operations were performed on the control group. Those in experimental group Data gathering was carried out using a demographic questionnaire and ENRICH marital satisfaction scale  Data analysis was carried out using SPSS version 24 software and descriptive and inferential statistical methods (MANCOVA). Results: Descriptive findings showed that the mean (standard deviation) of the total score of the marital satisfaction variable in the pre-test and post-test stages was 131.60 (26.89) and 142.81 (25.24) in the experimental group and 132.66 (24.09) and 132.26 (21.92) in the control group, respectively.The inferential findings showed that Bowen's family therapy approach has a significant effect on some of the dimensions of marital satisfaction (religious orientation, equality of women and men, children and parenting, sexual relation, financial management, conflict resolution, and marital satisfaction) (p< 0.05). On the other hand, this approach was not practical in improving other aspects of marital satisfaction (relationship with family and friends, leisure time, marital relationship, personality issues, and contractual responses) (p> 0.05). Conclusion: The present study results showed an increase in marital satisfaction of married women using the Bowen family therapy approach. Therefore, it is recommended to use Bowen's family therapy approach to improve women's marital satisfaction with family problems